2022
DOI: 10.1097/md.0000000000031166
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem as a cyclosporine A-sparing agent in heart transplantation: Benefits beyond dose reduction

Abstract: Diltiazem (DZ) is widely prescribed in transplant recipients because of its drug-drug interactions with calcineurin inhibitors (CNI). However, these interactions have been primarily investigated in renal transplantation, and data regarding the long-term efficacy and safety of DZ in orthotopic heart transplantation (OHT) are still sparse. Our study aimed to elucidate the extent to which the co-prescription of DZ reduces the dose required to maintain adequate blood levels of cyclosporine A (CsA) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A serious side effect is the worsening of kidney function [68]. It has been found that the use of diltiazem helps to maintain cyclosporine levels with lower doses of administration, protecting kidney function [71]. From studies, tacrolimus seems to be superior, especially in terms of side effects [72].…”
Section: Calcineurins Inhibitorsmentioning
confidence: 99%

Heart Transplantation

Chrysakis,
Magouliotis,
Spiliopoulos
et al. 2024
JCM
“…A serious side effect is the worsening of kidney function [68]. It has been found that the use of diltiazem helps to maintain cyclosporine levels with lower doses of administration, protecting kidney function [71]. From studies, tacrolimus seems to be superior, especially in terms of side effects [72].…”
Section: Calcineurins Inhibitorsmentioning
confidence: 99%

Heart Transplantation

Chrysakis,
Magouliotis,
Spiliopoulos
et al. 2024
JCM